Respuesta :

To simplify the following expression, we first simplify the terms inside the parenthesis from inner going outer. The first one is [p - (m + n - p)] equal to p - m- n + p = 2p - m - n. Then, n +2p - m - n equal to 2p -m. Then, m -  2p + m equal to 2m -2p. Answer is B

Answer:  The correct option is (b) [tex]2m-2p.[/tex]

Step-by-step explanation:  We are given to simplify the following expression:

[tex]E=m-\{n+[p-(m+n-p)]\}[/tex]

We will be using the simple algebraic operations and the rule of BODMAS to simplify the above expression.

The simplification is as follows:

[tex]E\\\\=m-\{n+[p-(m+n-p)]\}\\\\=m-\{n+[p-m-n+p]\}\\\\=m-\{n+[2p-m-n]\}\\\\=m-\{n+2p-m-n\}\\\\=m-\{2p-m\}\\\\=m-2p+m\\\\=2m-2p.[/tex]

Therefore, the simplified form is [tex]2m-2p.[/tex]

Thus, (b) is the correct option.

ACCESS MORE